Sedimentary facies analysis of the fluvial systems in the Siwalik Group, Karnali River section, Nepal Himalaya, and their significance for understanding the paleoclimate and Himalayan tectonics (Journal of Nepal Geological Society, 2016)
Fluvial sediments of the Siwalik successions in the Himalayan Foreland Basin are one of the most important continental archives for the history of Himalayan tectonics and climate change during the Miocene Period. This study reanalyzes the fluvial facies of the Siwalik Group along the Karnali River, where the large paleo-Karnali River system is presumed to have flowed. The reinterpreted fluvial system comprises fine-grained meandering river (FA1), flood-flow dominated meandering river with intermittent appearance of braided rivers (FA2), deep and shallow sandy braided rivers (FA3, FA4) to gravelly braided river (FA5) and finally debris-flow dominated braided river (FA6) facies associations, in ascending order. Previous work identified sandy flood-flow dominated meandering and anastomosed systems, but this study reinterprets these systems as a flood-flow dominated meandering river system with intermittent appearance of braided rivers, and a shallow sandy braided system, respectively. The order of the appearance of fluvial depositional systems in the Karnali River section is similar to those of other Siwalik sections, but the timing of the fluvial facies changes differs. The earlier appearance (3-4 Ma) of the flood-flow dominated meandering river system in the Karnali River section at about 13.5 Ma may have been due to early uplift of the larger catchment size of the paleo-Karnali River which may have changed the precipitation pattern i.e. intensification of the Indian Summer Monsoon. The change from a meandering river system to a braided river system is also recorded 1 to 3 Ma earlier than in other Siwalik sections in Nepal. Differential and diachronous activities of the thrust systems could be linked to change in catchment area as well as diachronous uplift and climate, the combination of which are major probable causes of this diachronity.